Extracorporeal Carbon Dioxide Removal - Fanelli, Vito (Critical Care Nephrology, 2019)
Mechanical ventilation (MV) represents a lifesaving treatment for patients with respiratory failure, but it could be harmful through the development of ventilator-induced lung injury (VILI). In patients with acute respiratory distress syndrome (ARDS), protective MV strategies with low tidal volume to minimize VILI have been demonstrated to reduce lung injury and mortality. However, they can be limited by the emergence of uncontrolled hypercapnia. Similarly, in COPD patients, noninvasive MV failure often is associated with a progressive rise in arterial CO(2) and need for endotracheal intubation, with higher risk of hospital mortality. Minimally invasive extracorporeal CO(2) removal systems (ECCO(2)R) theoretically can remove the entire amount of the CO(2) produced in the body per minute. In ARDS patients, ECCO(2)R may further reduce the risk of VILI ensuring ultraprotective MV and avoiding hypercapnia. In patients with exacerbation of COPD, ECCO(2)R may help to avoid intubation or facilitate weaning from invasive MV. In intensive care unit, concomitant renal and respiratory failure with MV is one of the strongest risk factors for hospital mortality. Combining ECCO(2)R and renal replacement therapy may support respiratory and renal functions and limit the side effects of MV. However, the need for systemic anticoagulation and the related risk of bleeding still represent a concern for a wider application of ECCO(2)R devices. In conclusion, ECCO(2)R is an effective support therapy to MV to limit its invasiveness and side effects, but its efficacy and safety must be proven in well-designed clinical trials.